Spatiotemporal variations in habitat quality and their determinants in the Henan Section of the Yellow River Basin - ZHANG Yingying; MA Ziyan; YU Nan; WEI Dechao; CHEN Zhaojing; YUAN Shuting; WANG Zheng; SONG Xinxin; ZHAO Yongqiang (Guan'gai paishui xuebao)
【Objective】The ecological functions of the Yellow River Basin have undergone significant changes in recent decades due to both natural and anthropogenic influences. In this paper, we analyze the spatiotemporal variation in habitat quality within the Henan Section of the basin from 1990 to 2020 to help ecological restoration and sustainable development in the region. 【Method】Habitat quality was assessed using the habitat quality module in the InVEST model and spatial autocorrelation analysis in GIS. Key determinants of spatiotemporal variation were identified using the Geodetector method.【Result】Over the past 30 years, the study area experienced a marked reduction in cultivated land and grassland, alongside a more than twice increase in construction land. The average habitat quality in the Henan Section was moderate, generally higher in the west and lower in the east. From 1990 to 2020, habitat quality exhibited strong spatial clustering, despite year-to-year fluctuations. Land use type was the primary driver of habitat quality change. Interaction effects between land use and variables such as elevation, temperature, NDVI, slope, precipitation, GDP, and population density all had explanatory power exceeding 0.95.【Conclusion】 Habitat quality in most parts of the Henan Section of the Yellow River Basin remained low from 1990 to 2020, with the decline closely linked to the expansion of construction land, particularly in urban areas. Science-based land use planning is essential to improving habitat quality and ensuring ecological sustainability of the region.